Professional identity in early practices: qualitative study with pedagogy students - Pereira-Bravo, Camila (2022)
Background: Achieving high quality teacher training requires teachers to have the opportunity to develop not only professional skills but also, fundamentally, their professional identity. Objective: To describe and interpret the subjective theories of Basic General Education Pedagogy students from a public university in northern Chile regarding the construction of professional identity in early practices. Method: A qualitative case study methodology was used with a theoretical sample of nine Basic General Education Pedagogy students from a public university in northern Chile. The data, obtained from episodic interviews and a group interview, was analyzed based on the grounded theory. Results: The following was found: (a) different meanings about early practice and an evaluation that includes positive and negative aspects of the process, (b) an association between the development of professional identity and the experience of implementing early practice, (c) a set of conditions that gather early practices to favor the construction of the professional identity and (d) the proposal for planning early practices as an experience different from the operation of the other subjects of the degree program. The foregoing was integrated into a comprehensive theory of the development of professional teacher identity in early practices. Discussion: In the discussion section, these results are analyzed from the existing literature. Authorship contribution CPB, MRF, AUV and DCM: study design, data processing and interpretation, introduction, results, discussion, general review and writing in APA format. PCC, IGP and JSD: introduction, discussion, general review.